Social Media and the Historical Trajectory of Political Violence in Aramoko-Ekiti, Ekiti State - Ojo, Christopher Mayowa (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
The intersection of communication networks and political violence has a long history in the Nigerian nation, where practices of information sharing have often informed collective action and conflict. In the Aramoko-Ekiti community, Ekiti State, Nigeria, community narratives, rumour networks, and partisan mobilisation have traditionally influenced political violence. The older channels have now gained new forms and terms with the emergence of social media, which has redefined the nature of political contestation. This paper is a critical assessment of how social media has contributed to the current phenomenon of political violence in Aramoko-Ekiti, especially with emphasis on the youth. Using a qualitative historical method, the study integrates oral interviews of sampled youth and political stakeholders, as well as the examination of secondary data in the form of online resources and digital communications. This approach situates the modern experience within the broader historical context of political agitation and violence in society. Social media platforms have altered the magnitude, pace, and intensity of mobilization, while also reproducing prior trends of competition and factionalism in the political trajectory of Aramoko-Ekiti, as revealed by the findings of this paper. The paper suggests encouraging historical consciousness, digital literacy, and responsible Internet use as measures to mitigate the adverse impact of violence and facilitate peaceful participation in the online space. Furthermore, it highlights the need for further research in this area to fully comprehend the intricate dynamics of social media and political violence. Keywords: Social media, Political violence, Youth, Aramoko-Ekiti, Digital Communication.